Research manufacturing process of corrugated packaging products - Гумен, Олена Миколаївна; Гумен, Степан Миколайович; Яблонський, Петро Миколайович (Eastern-European Journal of Enterprise Technologies, 2013)
Recently it has been preferred packaging of corrugated cardboard and cardboard. Although the material of the packing will be made depending on the product that will be in it, and its characteristics. Nowadays the most common packaging material is cardboard. Notable among different types of this material is corrugated paperboard profile (corrugated cardboard). Modern printed packaging products are made from various grades of paper and paperboard. Great demand today is cardboard and corrugated packaging quality, primarily because consumers pay attention to the type of packaging. To ensure proper packaging of products, it is necessary to analyze the materials and the type of required packaging products and manufacturing quality control stages. Such quality control can eliminate potential problems in the manufacturing process with minimal losses. After considering the method of manufacturing of corrugated cardboard in this paper was built a block diagram of the process of manufacturing three-layer corrugated board and developed an algorithm for the process of manufacturing of corrugated cardboard packaging. Proper tracking of each stage of the manufacturing process allows us to determine what quality may suffer in the future, and to find the optimum how to fix this.